2018
DOI: 10.1155/2018/9548471
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Associated Factors of Depression in an Asian Community in Dar es Salaam, Tanzania

Abstract: Depression is a common condition in developed countries and is a growing problem in developing countries like Tanzania. Various risk factors have been identified through different studies. This study aimed at finding the prevalence of depression in a predominantly migrant Asian community and the behavioral, familial, social, and medical factors influencing it. A cross-sectional study among adults in a closed Asian community was done. Interviews and self-administered questionnaires were used to obtain details o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 12 publications
(14 reference statements)
1
6
0
Order By: Relevance
“…Similarly, family history of depression was associated with antenatal depression; this finding is similar with the studies done in Dare Salam Tanzania [ 48 ]; an umbrella review on the global burden of antenatal depression [ 31 ], the study was done in Arba Minch [ 49 ] and Mizan Aman [ 50 ]. This could be explained by the role of genetics and psychosocial support system of the family dynamics that could contribute to the development of depression during pregnancy [ 51 ].…”
Section: Discussionsupporting
confidence: 80%
“…Similarly, family history of depression was associated with antenatal depression; this finding is similar with the studies done in Dare Salam Tanzania [ 48 ]; an umbrella review on the global burden of antenatal depression [ 31 ], the study was done in Arba Minch [ 49 ] and Mizan Aman [ 50 ]. This could be explained by the role of genetics and psychosocial support system of the family dynamics that could contribute to the development of depression during pregnancy [ 51 ].…”
Section: Discussionsupporting
confidence: 80%
“…This finding was supported by another study, which stated that economic status was negatively associated with depression [38]. Workers with insufficient monthly income were associated with depression [39]. Having a limited monthly income to support the family might affect living conditions and not fulfill basic needs; therefore, depression might be developed.…”
Section: Discussionmentioning
confidence: 62%
“…Our study found relatively higher levels of depression among this subpopulation compared with studies done among the general population in SSA. 28 29 The nature of police work has been found to explain this difference. First-line crisis responders were shown to have higher levels of depression and PTSD as a result of dealing with violent acts, death and abuse during work duties which can be psychologically stressful.…”
Section: Discussionmentioning
confidence: 99%